Who is a Journalist? A Critical Analysis of Australian Statutory Definitions. (December 2022) - Ananian-Welsh, Rebecca
This article provides the first comprehensive study of statutory definitions of 'journalist' and 'journalism' in Australian law and proposes a preferred definition of journalist by reference to statutory aims, bedrock legal principles and broader scholarship. It begins with a review of existing literature on the meaning of 'journalist' in the modern media landscape, before turning to Australian law. A qualitative survey of legislation identified 11 textually different definitions of the term 'journalist' across 18 separate statutes, and a single definition of 'journalism'. Examination of the statutory contexts, purposes and framing of these definitions reveals they are comprised, broadly, of six 'approaches'. These approaches are critically analysed against a novel five-part thematic framework, with particular attention given to whether journalists should be defined by reference to ethical codes and responsibilities. The article concludes by identifying a preferred definition of journalist capable of informing law reform across a wide-variety of areas of law, including protections for press freedom, journalistic access to information, shield laws and whistleblower protections.